B-Type Cardiac Natriuretic Peptides in the Neonatal and Pediatric Intensive Care Units - Cantinotti, Massimiliano (J Pediatr Intensive Care, 2016)
During the last decade, interest in the brain natriuretic peptide (BNP) and N-terminal probrain natriuretic peptide (NT-proBNP) in the pediatric population has progressively increased. The aim of this article is to provide an up to date review of evidences regarding the use of BNP/NT-proBNP in pediatrics, with a particular focus on neonatal intensive care and congenital heart disease. The potentialities of the BNP have been demonstrated in multiple settings, particularly: the screening of congenital/acquired heart disease (CHD) versus pulmonary disease; the evaluation of CHD severity (grade of heart failure, degree of left-to-right shunts); the management of children undergoing cardiac surgery; and monitoring premature infants with patent arterial duct. BNP/NT-proBNP values may be considered an easy and relatively low cost additional diagnostic and prognostic tool. Interpretation of BNP values in children requires attention to important factors, including: laboratory methods, the type of cardiac defect, its severity, and the presence of extracardiac conditions. Of these, the hemodynamic characteristic of CHD and physiologic variations of BNP values occurring during the first weeks of life play a major role. The current evidences in favor of BNP use are mainly derived from single-center, nonrandomized studies, and cost-effectiveness analysis are still lacking. As such, despite sufficient evidences supporting the diagnostic and prognostic potentialities of BNP, these findings should be reinforced by multicenter, randomized studies specifically designed to evaluate outcomes and cost-effectiveness. In addition, standard consensus documents/guidelines, that are currently lacking, are warranted for a more systematic use of BNP in the pediatric age.